Public vs. private the early history of school choice in America - Gross, Robert N. ca. 20./21. Jh (Oxford University Press, 2017)
Americans today choose from a dizzying array of schools, loosely lumped into categories of 'public' and 'private'. How did these distinctions emerge in the first place, and what do they tell us about the more general relationship in the United States between public authority and private enterprise? 'Public vs. Private' describes how nineteenth-century public policies fostered the rise of modern school choice